Fate of Selenate and Selenite Metabolized by Rhodobacter sphaeroides - Van Fleet-Stalder, Verena (American Society for Microbiology, 2000)
Cultures of a purple nonsulfur bacterium, Rhodobacter sphaeroides, amended with ∼1 or ∼100 ppm selenate or selenite, were grown phototrophically to stationary phase. Analyses of culture headspace, separated cells, and filtered culture supernatant were carried out using gas chromatography, X-ray absorption spectroscopy, and inductively coupled plasma spectroscopy-mass spectrometry, respectively. While selenium-amended cultures showed much higher amounts of SeO(3)(2−) bioconversion than did analogous selenate experiments (94% uptake for SeO(3)(2−) as compared to 9.6% for SeO(4)(2−)-amended cultures from 100-ppm solutions), the chemical forms of selenium in the microbial cells were not very different except at exposure to high concentrations of selenite. Volatilization accounted for only a very small portion of the accumulated selenium; most was present in organic forms and the red elemental form.